Running Collaborative Competence Groups - Exploring Experiences From Five Countries - Vibeke Krane; Ewelina Zubala; Thomas H. Thorning; Elena Quintana Murci; Eunice Macedo (International Journal of Qualitative Methods)
Collaborative competence group (CCG) is a research method within the collaborative research tradition. These groups are in line with a co-creation approach in which multiple stakeholders contribute to finding solutions to shared problems. Although CCGs have increased in use over the past decades, research on this method is limited. In this article, we explore and discuss the development and work in CCGs in an Erasmus + founded project: Co-creation through social inclusion in education (COSI.ed). The CCGs have been conducted in five countries over a three-year period: Denmark, Norway, Poland, Portugal and Spain. We have analyzed documents used in the CCG work and focus group discussions among the CCG facilitators. The findings show how it is essential to recruit adequate stakeholders and how the network can contribute as gatekeepers in this identification. Preparation for the CCG meetings is essential, and a close collaboration with the main project team is crucial. A feedback loop is created by requesting feedback from the main project team and bringing back feedback from the CCG discussions. The facilitators experienced that it could be challenging to involve all stakeholders in the discussions. We discuss how it is possible to foster solutions for sustainable CCGs. We also discuss the challenges and possibilities associated with the facilitator role. Moreover, challenges related to the power imbalance are discussed. We conclude that CCGs can be used as a tool for co-creation in collaborative research within a broad range of disciplines.